Role of MicroRNA-214 in Renal Ischaemia Reperfusion injury and fibrosis - Banwell, Victoria Carmen (The University of Edinburgh, 2021)
Organ transplantation is the gold standard treatment of end stage renal failure and has been shown to be superior to dialysis in terms of quality of life and life expectancy. Ischaemia is an inevitable consequence of renal transplantation and in particular, prolonged ischaemia is an independent risk factor for poor short- and long-term graft function and is associated with a higher rate of graft attrition. Chronic allograft damage is characterised by interstitial fibrosis and tubular atrophy and is the leading cause of late graft failure. At present this accounts for 5% of all kidney grafts lost annually and there are no treatments available. MicroRNAs (miRs) are short non-coding single strands of RNA that can inhibit gene expression by post-transcriptional repression or degradation of target mRNAs. MiR synthesis is tightly regulated under physiological conditions but can rapidly become dysregulated in injury. MiRs have been shown to play an important role in native renal disease and in particular miR-214 is associated with renal injury and fibrosis but its role in early injury and transition towards fibrosis remained unclear. The aim of this project was to investigate the role of miR-214 in early ischaemia reperfusion injury (IRI) and transition towards fibrosis using a murine model of IRI. There are various models of IRI that can be adopted: in this thesis a unilateral model of IRI was adopted in order for the animal to survive beyond the early phase of renal failure. 18 minutes of unilateral renal ischaemia induced significant fibrosis within the kidney after 14 days and peaked at 21 days. Following characterisation of the model, miR-214 expression from whole kidney tissue was examined at 2, 7, 14, 21 and 28 days to test the hypothesis that miR-214 was associated with early injury and fibrosis following IRI. 18 minutes of IRI resulted in significant acute kidney injury and upregulation of pro-inflammatory markers. Kidneys demonstrated rapid progression towards fibrosis as assessed by histology and confirmed by upregulation of pro-fibrotic gene expression. Importantly, miR-214 was increased during the early phase of injury and remained elevated at later time points, peaking at 5.5 fold increase in expression at 21 days (p<0.0001). Furthermore, miR-214 was upregulated 3.6 fold in CD3+ T-cell populations at 7 days (p<0.01) and 15 fold in F4/80hi macrophages at 21 days (p<0.001). Having shown that miR-214 was significantly upregulated at both early injury and later fibrosis, the effect of miR-214 ablation was examined by comparing outcomes of IRI in miR-214-/- and miR-214+/+ mice at 2 and 21 days to test the hypothesis that miR-214 blockade was protective against injury. MiR-214 deletion did not result in significant improvement in early injury markers at 2 days however there was a significant reduction in pro-inflammatory gene expression. At 21 days, there was evidence of improved tubular recovery and a 79% reduction in fibrosis on histology along with significant reduction of pro-fibrotic and pro-inflammatory gene expression in miR-214-/- mice. Flow cytometry showed no difference in CD3+ T-cell populations but a significant reduction in CD4+ T-cells from whole kidney tissue in miR-214-/- mice at 21 days potentially suggesting a role of miR-214 in T-cell populations in the kidney.
Keywords: kidney transplant scarring; microRNA-214; miR-214; fibrosis